The DNA resection protein CtIP promotes mammary tumorigenesis - Reczek, Colleen R. (Oncotarget, 2016)
Many DNA repair factors act to suppress tumor formation by preserving genomic stability. Similarly, the CtIP protein, which interacts with the BRCA1 tumor suppressor, is also thought to have tumor suppression activity. Through its role in DNA end resection, CtIP facilitates DNA double-strand break (DSB) repair by homologous recombination (DSBR-HR) and microhomology-mediated end joining (MMEJ). In addition, however, CtIP has also been implicated in the formation of aberrant chromosomal rearrangements in an MMEJ-dependent manner, an activity that could potentially promote tumor development by increasing genome instability. To clarify whether CtIP acts in vivo to suppress or promote tumorigenesis, we have examined its oncogenic potential in mouse models of human breast cancer. Surprisingly, mice heterozygous for a null Ctip allele did not display an increased susceptibility to tumor formation. Moreover, mammary-specific biallelic CtIP ablation did not elicit breast tumors in a manner reminiscent of BRCA1 loss. Instead, CtIP inactivation dramatically reduced the kinetics of mammary tumorigenesis in mice bearing mammary-specific lesions of the p53 gene. Thus, unlike other repair factors, CtIP is not a tumor suppressor, but has oncogenic properties that can promote tumorigenesis, consistent with its ability to facilitate MMEJ-dependent chromosomal instability. Consequently, inhibition of CtIP-mediated MMEJ may prove effective against tumor types, such as human breast cancer, that display MMEJ-dependent chromosomal rearrangements.